PREVENTING FRAUD WITH FORENSIC AUDITS, COMPETENT AUDITORS AND WHISTLEBLOWING SYSTEMS: THE ROLE OF AN ORGANIZATION'S ETHICAL CULTURE - Risma Aditama; Yana Ulfah; Ledy Setiawati (University of Widya Gama Mahakam Samarinda, 2026)
Fraud prevention is a crucial effort in strengthening accountability and integrity within public sector organizations. This study aims to examine the effect of forensic audit, auditor competence, and whistleblowing system on fraud prevention through organizational ethical culture as a mediating variable at the East Kalimantan Provincial Inspectorate. This research employed a quantitative approach with a causal research design. The population consisted of 81 auditors working at the East Kalimantan Provincial Inspectorate. Using a purposive sampling technique, 81 questionnaires were distributed, 78 were returned, and 63 valid responses were analyzed, resulting in a response rate of 77.8%. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that forensic audit, auditor competence, and whistleblowing system have a positive and significant effect on organizational ethical culture. Furthermore, forensic audit, auditor competence, and organizational ethical culture have a positive and significant effect on fraud prevention, whereas the whistleblowing system does not have a significant direct effect on fraud prevention. Organizational ethical culture was found to mediate the relationship between forensic audit, auditor competence, and whistleblowing system and fraud prevention. These findings suggest that strengthening forensic audit practices, enhancing auditor competence, and fostering an ethical organizational culture are essential strategies for improving fraud prevention within public sector organizations.